PENGOLAHAN LIMBAH MENJADI MAKANAN RINGAN DI DESA TIKUSAN KECAMATAN KAPAS KABUPATEN BOJONEGORO - Firda Zakiyatur Rofi’ah; Wahyu Setia Kuscahyaning Putri; Suttrisno (Mafaza : Jurnal Pengabdian Masyarakat, 2021)
Tikusan Village is one of the villages located ini Kapas District, Bojonegoro Regency. This village has vilaage assets, namely land resources in the form of a home industry (tofu and tempeh industry). ). Therefore, the community assistance method used is the ABCD (Asset Based Community Development) method. The community service program is carried out by a team of lecturers and students of UNUGIRI Bojonegoro in collaboration with the local village community. This assistance produces snack products, such as: debog chips, tofu crackers, sandwiches and corndogs from tofu dregs. The existence of these processed products is expected to be a solution to the presence of abundant assets which are considered as waste, making them less valuable.